2024
DOI: 10.1172/jci174186
|View full text |Cite
|
Sign up to set email alerts
|

Dietary dicarboxylic acids provide a nonstorable alternative fat source that protects mice against obesity

Eric S. Goetzman,
Bob B. Zhang,
Yuxun Zhang
et al.

Abstract: Dicarboxylic fatty acids are generated in the liver and kidney in a minor pathway called fatty acid ωoxidation. The effects of consuming dicarboxylic fatty acids as an alternative source of dietary fat have not been explored. Here, we fed dodecanedioic acid, a 12-carbon dicarboxylic (DC12), to mice at 20% of daily caloric intake for nine weeks. DC12 increased metabolic rate, reduced body fat, reduced liver fat, and improved glucose tolerance. We observed DC12-specific breakdown products in liver, kidney, muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
(89 reference statements)
1
4
0
Order By: Relevance
“…The paradigm of nutrient composition acknowledges only three energy substrates: glucose, amino acids, and fatty acids. In this issue of the JCI, Goetzman et al, ( 2 ) confirmed and magnified the evidence of previous investigations establishing the presence and metabolic importance of a fourth nutrient, DAs. While metabolizable DAs are classified as medium-chain fatty acids, they possess two terminal carboxylic groups that permit the formation of dicarboxylic salts, making them easily soluble in water and promptly available as energy.…”
Section: Dicarboxylic Acids As the Missing Fourth Nutrientsupporting
confidence: 62%
See 4 more Smart Citations
“…The paradigm of nutrient composition acknowledges only three energy substrates: glucose, amino acids, and fatty acids. In this issue of the JCI, Goetzman et al, ( 2 ) confirmed and magnified the evidence of previous investigations establishing the presence and metabolic importance of a fourth nutrient, DAs. While metabolizable DAs are classified as medium-chain fatty acids, they possess two terminal carboxylic groups that permit the formation of dicarboxylic salts, making them easily soluble in water and promptly available as energy.…”
Section: Dicarboxylic Acids As the Missing Fourth Nutrientsupporting
confidence: 62%
“…Another important advantage of dietary DC12 over fatty acids that was highlighted in Goetzman et al ( 2 ) is its storage; DC12 was not stored intracellularly and thus it did not promote fat deposition. In other words, DAs are completely oxidized either in mitochondria or in peroxisomes ( Figure 1 ).…”
Section: Dc12 Improves Insulin Resistance and Increases Energy Expend...mentioning
confidence: 97%
See 3 more Smart Citations